Neurochemical research in autism - Anderson, George (Henry Stewart Talks, 2010)
Overview of neurochemical research in autism, Acetylcholine, Glutamate, GABA, Endogenous opioids, Oyxtocin & AVP, Dopamine, Stress response systems, Noradrenergic/sympathetic nervous system, The adrenomedullary system and the HPA axis, Serotonin and melatonin